2021
DOI: 10.1111/jpr.12365
|View full text |Cite
|
Sign up to set email alerts
|

Japanese Version of the Eyberg Child Behavior Inventory: Translation and Validation1

Abstract: This study assessed the psychometric properties of the Japanese version of the Eyberg Child Behavior Inventory (ECBI) in children in clinical and non‐clinical settings in Japan. Validation of the ECBI for clinical and non‐clinical participants (N = 128, 2–7 years of age) was evaluated. First, we evaluated the internal consistency reliability of the ECBI Problem and Intensity scales. We evaluated the construct and criterion‐referenced validity by comparing scores among the subscales of the ECBI, Child Behavior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…Questionnaires from all 1,992 participants were included in the data analysis. The strong reliability found for the ECBI scales replicated findings from the Kamo et al study 23 in this large normative sample of children and their parents in Japan. To verify the normality of our sample, we examined a histogram of ECBI Intensity scores.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Questionnaires from all 1,992 participants were included in the data analysis. The strong reliability found for the ECBI scales replicated findings from the Kamo et al study 23 in this large normative sample of children and their parents in Japan. To verify the normality of our sample, we examined a histogram of ECBI Intensity scores.…”
Section: Discussionsupporting
confidence: 82%
“…21 In Japan, we conducted a validation study of 128 children aged 2-7 years using the Japanese version of the ECBI as a preliminary study. 22 The results from that study also found that Cronbach's a for the ECBI Intensity and the Problem Scales was 0.91 and 0.92, respectively, reflecting the high internal consistency found in many studies. 7,[12][13][14][15][16][17][18] As mentioned above, normative ECBI data has been established in several countries, but there has been no large-scale survey in Japan, and therefore cutoff points for the identification of clinically significant behavior problems among Japanese children have not yet been established.…”
mentioning
confidence: 69%
See 3 more Smart Citations